(untitled) (Nordic Journal of African Studies, 2005)
Many scholars before this time have written about the Ogboni institution in Yoruba land of southwest Nigeria. Instances are William Bascom (1944); Forde (1951); Peter Morton-Williams (1960); J.R.O. Ojo (1972–73); Robert Smith (1976); L.E. Roache (1971); R. Hallgren (1988). However, conspicuously missing in their analyses is the overriding influence and place that the Ogboni institution wields in the conception of law and the moral life of the community. Previous analyses have tended only to incorporate or focus on the religious cum social influence of the Ogboni. Many of the accounts also seem to reflect, by way of allusion, references to their political functions. This paper is interested in establishing the nature and idea of law and morals in traditional Yoruba society seen from the perspective of the Ogboni group. What has the Ogboni phenomena and its operation with respect to the legal dimension of traditional life and Yoruba belief system got to contribute in the understanding of the relationship between law and morality?